HUBUNGAN PENDAPATAN KELUARGA DENGAN ASUPAN GIZI ENERGI, PROTEIN, ZAT BESI, VITAMIN A IBU HAMIL DI PUSKESMAS UMBAN SARI KOTA PEKANBARU - Saputri, Febrima; Restuastuti, Tuti; Christanto, Erwin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
The intake of nutrients on pregnant women is composed of micro nutrientsand macro nutrients. Micro nutrients namely vitamins (vitamin A) and minerals(iron). While macro nutrients namely carbohydrates, fats and protein. The nutritionalintake of pregnant women are affected by a variety of internal and external factors oflevels of knowledge, social factors, and income factors of pregnant women. Thepurpose of this study is to discover the relationship between family income with thenutritional intake of energy, protein, iron and vitamin A of pregnant women. Thisstudy includes the type of analytic study using cross sectional approach. Totalsamples are 39 people, sampling technique is proporsional random sampling. Theresult showed that of the 39 respondents known as 30 people (76,9%) have a familyincome less than UMR. Analyzing data used Fisher test showed that there is asignificant relationship between family income with the nutritional intake of energy,protein, iron and vitamin A of pregnant women.Key words: family income, dietary energy, dietary protein, the nutritional intake ofiron, the nutritional intake of vitamin A